Effects of growth hormone on lipid metabolism and sexual development in pubertal obese male rats - Guo Shujuan; Zheng Juan; Li Guimei (Open Life Sciences, 2022)
To investigate the effects of growth hormone (GH) on pubertal obese male rats, a rat model of high-fat diet-induced obesity was established in juvenile male rats. The model rats were divided into the treatment group (GH) and the non-treatment group (physiological saline). After 4 weeks, we measured the levels of alanine transaminase (ALT), aspartate aminotransferase (AST), total cholesterol (TC), triglycerides (TGs), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), estrogen (E2), testosterone (T), and insulin-like growth factor (IGF-1). The morphological changes of the liver and testis were assessed, and the expression of aromatase was detected. The levels of ALT, AST, TC, TG, LDL-C, E2, and IGF-1 in the treatment group were significantly lower than in the non-treated model rats (P < 0.001). The levels of HDL-C and T of GH-treated rats were significantly higher than those of the non-treatment group (P < 0.001). Compared with non-treated model rats, GH-treated model rats showed reduced liver steatosis, improved morphological structure of the testicular seminiferous tubules, and an increased number of spermatogenic cells. The treatment group also showed lower expression of aromatase in the liver and testis compared with the non-treatment group. GH partially protected pubertal male rats from obesity-induced lipid metabolic disorder and sexual retardation.